2019
DOI: 10.1177/0194599819866692
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of High‐Throughput DNA Sequencing of the Paranasal Sinus Microbiome in Diagnosing Odontogenic Sinusitis

Abstract: Objective High-throughput DNA sequencing of the paranasal sinus microbiome has potential in the diagnosis and treatment of sinusitis. The objective of this study is to evaluate the use of high-throughput DNA sequencing to diagnose sinusitis of odontogenic origin. Study Design Case series with chart review. Setting Single tertiary care academic medical center. Subjects and Methods A chart review was performed of DNA sequencing results from the sinus aspirates obtained under endoscopic visualization in 142 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Regarding similarities, multiple uncomplicated ODS studies have shown higher rates of certain anaerobic and α-hemolytic streptococcal species in sinus cultures. 6,38-40 These prior studies typically included patients with chronic symptoms, but the current review showed very similar microbiology in patients with acute presentations. Similarly, Brook 41 demonstrated no significant differences in sinus cultures between ODS patients with acute vs chronic symptoms, and therefore ODS microbiology may be stable over time.…”
Section: Discussionmentioning
confidence: 67%
“…Regarding similarities, multiple uncomplicated ODS studies have shown higher rates of certain anaerobic and α-hemolytic streptococcal species in sinus cultures. 6,38-40 These prior studies typically included patients with chronic symptoms, but the current review showed very similar microbiology in patients with acute presentations. Similarly, Brook 41 demonstrated no significant differences in sinus cultures between ODS patients with acute vs chronic symptoms, and therefore ODS microbiology may be stable over time.…”
Section: Discussionmentioning
confidence: 67%
“…One’s suspicion of ODS would additionally increase if sinus cultures revealed anaerobic or odontogenic bacteria. 6,4244 The current study suggests that if patients have unilateral maxillary sinus disease on sinus CT and pus in the middle meatus, one should consider an odontogenic source of the infection. Further prospective studies would also be beneficial in determining whether identifying unilateral middle meatal pus alone is predictive of ODS, when no CT is available.…”
Section: Discussionmentioning
confidence: 83%
“…Forty-nine studies reported specific diagnostic criteria 7,10,1662 and 14 studies did not report any diagnostic criteria (either original or referenced) for OS. 8,11,6374 It should be noted that four articles 10,21,31,39 were retrospective radiological analyses and provided radiologic diagnostic criteria only.…”
Section: Resultsmentioning
confidence: 99%